ANALISIS PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK PADA MATERI FUNGSI KOMPOSISI - Putri, Prima Septia (Jurnal Edukasi dan Penelitian Matematika, 2023)
This study aims to analyze the understanding of mathematical concepts of ten social class senior highschool  students on compositional function material. This research is a qualitative research with a descriptive approach. The research procedure includes the preparation stage, the implementation stage and the data analysis stage. The research subjects consisted of three students, the selection of research subjects was done by looking at students' math scores, namely the highest, average, and lowest grades in their class with the miminum mastery criteria score as a reference for assessment. The instrument used is a test of understanding mathematical concepts. The results of the study showed that students in ten grades three social enough to understand the compositional function material so that students have an understanding of mathematical concepts that are currently in the compositional function material..Keywords: Analysis of Students Mathematical Ability, Understanding of Mathematical Concepts, Composition Function Material